2012
DOI: 10.1371/journal.pone.0051645
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Nerve Fibre Layer Thinning in Patients with Clinically Isolated Optic Neuritis and Early Treatment with Interferon-Beta

Abstract: BackgroundOptic neuritis is associated with neurodegeneration leading to chronic impairment of visual functions.ObjectiveThis study investigated whether early treatment with interferon beta (IFN-β) slows retinal nerve fibre layer (RNFL) thinning in clinically isolated optic neuritis.MethodsTwenty patients with optic neuritis and visual acuity decreased to ≤0.5 (decimal system) were included into this prospective, open-label, parallel group 4-month observation. After methylprednisolone pulse therapy, 10 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 40 publications
2
17
0
Order By: Relevance
“…In contrast to the absence of axonal loss in amiodarone toxicity Sühs et al, studying demyelinating optic neuritis, showed that RNFL thinned to levels greater than 10 µm below the healthy eye after a transient oedema that resolved within the first two months after disease onset [11]. Similar to Sühs et al, our patient's RNFL showed an important elevation at baseline that returned to normal values after one month.…”
Section: Discussionsupporting
confidence: 77%
“…In contrast to the absence of axonal loss in amiodarone toxicity Sühs et al, studying demyelinating optic neuritis, showed that RNFL thinned to levels greater than 10 µm below the healthy eye after a transient oedema that resolved within the first two months after disease onset [11]. Similar to Sühs et al, our patient's RNFL showed an important elevation at baseline that returned to normal values after one month.…”
Section: Discussionsupporting
confidence: 77%
“…; Suhs et al . ). IL1RN, RANTES, and IFIT1 have neuroprotective activity against brain ischemia (Kaul and Lipton ; Mulcahy et al .…”
Section: Discussionmentioning
confidence: 97%
“…The neuroprotective functions of these IFN-related molecules have been identified in different ischemia/disorders models. The local administration of exogenous IFNb confers protection against brain ischemia and retinal disease (Veldhuis et al 2003;Marsh et al 2009;Suhs et al 2012). IL1RN, RANTES, and IFIT1 have neuroprotective activity against brain ischemia (Kaul and Lipton 1999;Mulcahy et al 2003;Emsley et al 2005;Sorce et al 2010;Szretter et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In cuprizone-induced demyelination, IFNβ-deficient mice showed accelerated remyelination of the corpus callosum [62], and long-term IFN-β treatment of mice aggravated viral-induced demyelination [63]. Conversely, no effect of IFN-β on ffVEP latency recovery or RNFL thinning was reported in a 16-week open label study of patients with clinically isolated optic neuritis [64].…”
Section: Discussionmentioning
confidence: 99%